2014
DOI: 10.1371/journal.pone.0115510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Texture Features Derived from Static and Respiratory-Gated PET Images in Non-Small Cell Lung Cancer

Abstract: BackgroundPET-based texture features have been used to quantify tumor heterogeneity due to their predictive power in treatment outcome. We investigated the sensitivity of texture features to tumor motion by comparing static (3D) and respiratory-gated (4D) PET imaging.MethodsTwenty-six patients (34 lesions) received 3D and 4D [18F]FDG-PET scans before the chemo-radiotherapy. The acquired 4D data were retrospectively binned into five breathing phases to create the 4D image sequence. Texture features, including M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 49 publications
5
56
2
Order By: Relevance
“…Furthermore, the statistical quality of PET images was shown to affect textural parameters to a lesser extent than respiratory motion, with no significant differences found between images of different statistical quality. The blurring effect of respiratory motion on quantification of intratumor heterogeneity was shown in studies by Yip et al (13), and Oliver et al (21). Although our results are in line with theirs, the observed differences between the respiratory gated and nongated PET images were usually small.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the statistical quality of PET images was shown to affect textural parameters to a lesser extent than respiratory motion, with no significant differences found between images of different statistical quality. The blurring effect of respiratory motion on quantification of intratumor heterogeneity was shown in studies by Yip et al (13), and Oliver et al (21). Although our results are in line with theirs, the observed differences between the respiratory gated and nongated PET images were usually small.…”
Section: Discussionsupporting
confidence: 90%
“…The accuracy and robustness of these measurements is related to the PET acquisition and reconstruction protocols, as well as variability in patient physiology. In particular, blurring of PET images due to respiratory motion can significantly influence quantification of lung lesions (12,13). In addition, PET textural parameters can be sensitive to variations in statistical quality and to normal stochastic variations in images (14).…”
mentioning
confidence: 99%
“…We chose to limit lesion size in order to reduce the influence of both respiratory motion and PVE. Although previous studies have shown variability in heterogeneity features as a result of respiratory gating (35,36), other studies have shown no statistically significant differences in the PET heterogeneity parameters considered in the present study (37). In addition, most of the lesions in our study (85%) were in the upper lung lobes, which are less influenced by respiratory motion.…”
Section: Discussioncontrasting
confidence: 70%
“…Second, partial-volume effects resulting from limited PET spatial resolution may lead to an underestimation of the metabolic tumor region and SUV measures (49). Furthermore, because of insufficient data acquisition and limited reconstruction techniques, respiratory motion can induce image blurring in the static (3-dimensional PET) image acquisition, subsequently affecting the quantification of the PET features (50). Despite these limitations, many radiomic features were still found to be significantly associated with and predictive of EGFR mutation status.…”
Section: Discussionmentioning
confidence: 99%